2023
DOI: 10.2147/ijn.s398254
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Modified Gold Nanoparticles as Novel Radiosensitizers for Enhancing Lung Cancer Radiotherapy

Abstract: Background Considering the strong attenuation of photons and the potential to increase the deposition of radiation, high-atomic number nanomaterials are often used as radiosensitizers in cancer radiotherapy, of which gold nanoparticles (GNPs) are widely used. Materials and Methods We prepared albumin-modified GNPs (Alb-GNPs) and observed their radiosensitizing effects and biotoxicity in human non-small-cell lung carcinoma tumor-bearing mice models. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Although their study effectively displayed the energy dependence of the radiosensitization due to GNPs, it suggested that GNPs were effective in increasing the radiosensitization of cells when treated with MV X-rays. These results have also been further corroborated by various studies that effectively display the sensitizing effects of high-Z NPs when irradiated by MV sources, indicating that other mechanisms could be responsible for the observed radiosensitization [20,[39][40][41][42].…”
Section: Physical Mechanism Of Np-based Radiosensitizationsupporting
confidence: 70%
“…Although their study effectively displayed the energy dependence of the radiosensitization due to GNPs, it suggested that GNPs were effective in increasing the radiosensitization of cells when treated with MV X-rays. These results have also been further corroborated by various studies that effectively display the sensitizing effects of high-Z NPs when irradiated by MV sources, indicating that other mechanisms could be responsible for the observed radiosensitization [20,[39][40][41][42].…”
Section: Physical Mechanism Of Np-based Radiosensitizationsupporting
confidence: 70%
“…Additionally, the albumin-AuNPs showed effective tumor accumulation. These findings highlight the potential for relatively greater radiosensitization and antitumor activity while minimizing damage to normal body tissues, but pharmacokinetic studies, validation of tumor models, and investigation of the mechanism of radiosensitization were lacking in this experiment [ 115 ].…”
Section: Research On Polysaccharide-aunps As Drug Delivery Carriersmentioning
confidence: 99%
“…They can locally enhance the efficacy of RT through their unique photoelectric properties and high X-ray absorption, which leads to increased radiation dose deposition in tumor tissues [ 10 ]. Various studies have demonstrated that GNPs can effectively sensitize tumor cells to radiation by generating reactive oxygen species (ROS) and other mechanisms that amplify DNA damage [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Recent advances in nanotechnology have facilitated the development of GNPs that are optimized for better dosing and higher therapeutic effects [ 13 , 15 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated that GNPs can effectively sensitize tumor cells to radiation by generating reactive oxygen species (ROS) and other mechanisms that amplify DNA damage [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Recent advances in nanotechnology have facilitated the development of GNPs that are optimized for better dosing and higher therapeutic effects [ 13 , 15 , 16 , 18 ]. Enhancing GNPs as radiosensitizers involves surface modifications with ligands like polyethylene glycol (PEG) for immune evasion and arginyl-glycyl-aspartic acid (RGD) for selective cancer cell targeting [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%